Spent-grains and zeolites as potential carriers for trypsin immobilisation - Rocha, Cristina M. R. (2005)
Trypsin is a widely used enzyme for protein hydrolysis and can be used to improve functional and nutritional properties of foods. The immobilization of enzymes on solid supports can offer several advantages over free enzymes including easy handling, recovery from the reaction medium, reuse and operation in continuous reactors. Traditional carriers include porous silica, porous glass and cellulose derivatives. Zeolites are porous alumino-silicates available in a wide range of particle size and porosity and can also be used as carriers. Spent grains are a brewing by-product with a high content in cellulose and can also be interesting as carriers for enzyme immobilization because, besides having the necessary conditions (as stability, rigidity, low mass transfer limitations, for instance), they are cheap and food grade. This work proposes the use of spent grains and zeolites as alternative carriers for trypsin immobilization and compares them with a traditional support (silica). Physical adsorption, ionic attachment and covalent attachment to the supports were tested. The efficiency of immobilization and activity, as well as the operation and storage stability of free and immobilized enzyme on the three supports were studied. Trypsin was most successfully immobilized on the supports by covalent attachment using glutaraldehyde. Though the best efficiencies were still obtained with silica, promising results were achieved with both spent grains and zeolite.